Study on Electrical Characteristics and ECG Signal Acquisition Performance of Fabric Electrodes Based on Organizational Structure and Wearing Pressure - Ming Wang; Jinli Zhou; Ge Zhang (Micromachines)
Obtaining stable ECG signals under both static and dynamic conditions, while ensuring comfortable wear, is a prerequisite for fabric-electrode applications. It is necessary to study the wearing pressure of fabric electrodes as well as their organizational structure. In this study, fabric electrodes with different organizational structures (plain weave, twill weave, and satin weave) were prepared using silver-plated nylon conductive yarns as weft yarns and polyester yarns as warp yarns. The electrical characteristics of these structures of fabric electrodes were analyzed under different wearing pressures (2 kPa, 3 kPa, 4 kPa, and 5 kPa), and their effects on the quality of static and dynamic ECG signals acquired from human body were examined. The results showed that the contact impedance of the twill and satin weave structured electrodes with the skin was smaller and more stable than that of the plain weave structured electrodes. Furthermore, when a wearing pressure of 3–4 kPa was applied to the satin-structured electrodes, they not only provided satisfactory comfort but also collected stable static and dynamic ECG signals during daily exercise. These results can provide a reference for the application of fabric electrodes in ECG monitoring devices and an important basis for the design of intelligent ECG clothing.